2019
DOI: 10.1080/21678421.2018.1556695
|View full text |Cite
|
Sign up to set email alerts
|

Primary progressive aphasia and the FTD-MND spectrum disorders: clinical, pathological, and neuroimaging correlates

Abstract: Objective: Behavioral variant frontotemporal dementia (bvFTD), is commonly considered the cognitive presentation of the frontotemporal dementia-motor neuron disease (FTD-MND) spectrum disorder. We evaluated the prevalence of primary progressive aphasia in a series of pathologically confirmed cases of FTD-MND spectrum. Methods: Pathologically confirmed cases of frontotemporal lobar degeneration-motor neuron disease (FTLD-MND) were obtained from the UCSF brain bank. Cases were analyzed for presence of language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(28 reference statements)
1
21
0
Order By: Relevance
“…Clinical and neuropsychological tests may reveal certain clues as to the underlying proteinopathy in PPA: non-verbal episodic memory deficits are associated with Alzheimer pathology [49], whilst Parkinsonism (often evolving into a progressive supranuclear palsy/corticobasal syndrome) and apraxia of speech are typically associated with a tauopathy [22, 23••]. Motor neuron disease features accompanying nfvPPA and svPPA may be under-recognised and predict underlying histopathology [50,51].…”
Section: The Challenge Of Molecular Diagnosis: Physiological Phenotypmentioning
confidence: 99%
“…Clinical and neuropsychological tests may reveal certain clues as to the underlying proteinopathy in PPA: non-verbal episodic memory deficits are associated with Alzheimer pathology [49], whilst Parkinsonism (often evolving into a progressive supranuclear palsy/corticobasal syndrome) and apraxia of speech are typically associated with a tauopathy [22, 23••]. Motor neuron disease features accompanying nfvPPA and svPPA may be under-recognised and predict underlying histopathology [50,51].…”
Section: The Challenge Of Molecular Diagnosis: Physiological Phenotypmentioning
confidence: 99%
“…That is: individuals with bvFTD manifest with dysexecutive and behavioral symptoms because neurons within specific regions of the brain underlying executive function and social behavior (e.g., anterior cingulate, frontoinsular, striatum, and amygdala regions) are impacted (Perry et al, 2017); individuals with svPPA manifest semantic loss because neurons within anterior temporal lobe related to semantic knowledge are impacted (Gorno-Tempini et al, 2011). Neuroimaging studies additionally support the notion of ALS and FTD as a continuum showing that motor cortex and anterior cingulate as well as their underlying white matter tracts are impacted in ALS patients, while widespread frontal, anterior cingulate, insular, and temporal lobes are impacted in ALS-FTD and bvFTD patients (Lillo et al, 2012;Crespi et al, 2018;Trojsi et al, 2018;Seeley, 2019;Vinceti et al, 2019). Furthermore, while most forms of ALS are due to pathological inclusions of TDP-43 (with some exceptions, noted in the next section), about half of all bvFTD (Neumann et al, 2006;Perry et al, 2017), most svPPA (Grossman, 2010;Josephs et al, 2011;Borghesani et al, 2020), and a portion of nfvPPA cases are due to TDP-43 (Adams-Carr et al, 2020).…”
Section: Clinical Phenotypes Of Ftd and Alsmentioning
confidence: 89%
“…People with FTD may also experience movement symptoms, such as bradykinesia, dystonia, rigidity, and apraxia, with 12.5% of patients with bvFTD meeting clinical criteria for either corticobasal syndrome (CBS) or progressive supranuclear palsy syndrome (PSPS) ( Ljubenkov and Miller, 2016 ). About 15% of people with bvFTD, 11% of patients with nfvPPA, and 19% of patients with svPPA may also eventually develop motor symptoms consistent with ALS ( Rascovsky et al, 2011 ; Vinceti et al, 2019 ).…”
Section: Clinical Phenotypes Of Ftd and Alsmentioning
confidence: 99%
“…ALS motor and cognitive manifestations can worsen in parallel, becoming more pronounced when bulbar functions (affecting speech, swallowing, and salivation) are involved [ 8 , 9 ]. Manera et al compared patients according to the lateralization of motor damage and found that spinal patients with symmetric motor impairment had significantly worse cognitive performance than those with lateralized damage [ 10 ].…”
Section: Prevalence Of Als-ftsdmentioning
confidence: 99%
“…These consisted of effortful speech, tongue weakness in nfvPPA-MND, and upper limb weakness with fasciculations in both groups. When looking at the timeline, the nfvPPA-MND cases developed severe motor deficits more rapidly than the svPPA-MND cases [ 9 ].…”
Section: Clinical Manifestations Of Als-ftsdmentioning
confidence: 99%